2019
DOI: 10.1101/678474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A chromosome folding intermediate at the condensin-to-cohesin transition during telophase

Abstract: Chromosome folding is extensively modulated as cells progress through the cell cycle. During mitosis, condensin complexes fold chromosomes in helically arranged nested loop arrays. In interphase, the cohesin complex generates loops that can be stalled at CTCF sites leading to positioned loops and topologically associating domains (TADs), while a separate process of compartmentalization drives the spatial segregation of active and inactive chromatin domains. We used synchronized cell cultures to determine how t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 61 publications
(40 reference statements)
4
30
0
Order By: Relevance
“…This is in agreement with single-cell Hi-C analysis in mouse embryonic stem cells, which showed that the B compartment (largely overlapping with LADs [4]) gradually moves towards a more radial positioning in early G1 [37]. Similarly, Hi-C in synchronized cells showed that chromatin compartments appear in telophase and gradually gain in strength [38,39].…”
Section: Cell Cycle Dynamics Of Genome -Nl Interactionssupporting
confidence: 89%
“…This is in agreement with single-cell Hi-C analysis in mouse embryonic stem cells, which showed that the B compartment (largely overlapping with LADs [4]) gradually moves towards a more radial positioning in early G1 [37]. Similarly, Hi-C in synchronized cells showed that chromatin compartments appear in telophase and gradually gain in strength [38,39].…”
Section: Cell Cycle Dynamics Of Genome -Nl Interactionssupporting
confidence: 89%
“…This is in agreement with single‐cell Hi‐C analysis in mouse embryonic stem cells, which showed that the B compartment (largely overlapping with LADs; van Steensel & Belmont, 2017) gradually moves toward a more radial positioning in early G1 (Nagano et al , 2017). Similarly, Hi‐C in synchronized cells showed that chromatin compartments appear in telophase and gradually gain in strength (Abramo et al , 2019; Zhang et al , 2019). Noteworthy, the self‐aggregation of LADs occurs before NL positioning (preprint: Luperchio et al , 2018), suggesting that the formation of the B compartment and NL positioning are correlated but still separate processes.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, LE activity of cohesin in vivo accounts for the peaks and strikes observed in Hi‐C matrices, which are commonly translated as topological associated regions (TADs) in G1 cells (Fudenberg et al, 2016, Sanborn et al, 2015). Recent studies confirmed that cohesin‐mediated loops and the positions of TADs emerge quickly after telophase by producing contact patterns consistent with a LE process (Abramo et al, 2019; Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 84%